Physico-chemical Amino acid composition, fatty acid profile, functional and antioxidant properties of Spinacia oleracea L. leaf - Pamidighantam, Prabhakara Rao; Galla, Narsing Rao; Guruguntla, Sulochanamma; Akula, Satyanarayana (Fakultas Farmasi, Universitas Gadjah Mada, 2015)
Spinach (Spinacia oleracea L.) leaf powder (SLP) was prepared and its physicochemical (proximate composition, colour, mineral content, EMC-RH, protein solubility, amino acid content and fatty acid profile), functional (water absorption, fat absorption, emulsification and foam capacities) and antioxidant (DPPH, ABTS and Iron reducing power) properties were studied. SLP possessed a protein content of 31.72%, calcium (1335 mg/100g), iron (29 mg/100g) and phosphorous (278 mg/100g). Moisture sorption isotherms of SLP indicated its non-hygroscopic nature. Solubility of SLP protein in distilled water was 39.66%, which got enhanced to 72.83% in 0.1M NaCl at pH 12. The spinach leaf lipid was found to be rich in Ï‰-3 fatty acids (67.4%). Leucine (11.87%), phenylalanine (5.9%) and valine (9.24%) were the major essential amino acids observed in SLP. Functional properties of SLP exhibited good water absorption, fat absorption and foam capacities. Antioxidant activity of SLP determined by the 2,2-azino-bis (3-ethyl benzothiazoline 6- sulphonic acid (ABTS) assay was found higher, when compared to the activities determined by diphenyl picrylhydrazyl (DPPH) and ferric reducing power assays. Protein solubility, amino acid content, fatty acid profile, functional properties and antioxidant characteristics encouraging for food and pharmaceutical applications.